Digital Marketing Strategies Driven by Wellbeing in Virtual Communities: Literature Review - Ayachi, Zeineb; Jallouli, Rim (Journal of Telecommunications and the Digital Economy, 2022)
In the new era ushered in by Covid-19, priority has been given to peoples’ wellbeing. Wellbeing in virtual communities was analysed from several perspectives, such as healthcare, technology, and social science: hence, the importance of a literature review that clarifies how studying health, happiness, comfort and quality of life of virtual communities’ members could guide firms to conceive their digital communication and marketing strategies. This work presents a literature review of papers spanning from 2010 to 2021, and which study digital marketing strategies driven by wellbeing in virtual communities. Results indicate a growing research interest after the pandemic regarding both positive and negative wellbeing dimensions, especially as drivers for digital segmentation, targeting and positioning strategies. Moreover, results highlight the remarkable increase of papers focusing on the tourism industry, game related strategies, and marketing analytics as relevant tools that support digital communication and influence strategies towards virtual communities. Finally, this literature review provides researchers with guidance for future studies in terms of relevant methodologies and areas of research not yet explored.